PEMILIHAN UMUM DAN DEMOKRASI : KEGAGALAN PEREMPUAN PADA PILEG 2019 KABUPATEN KERINCI - , S.IP, Wahyu Hidayat (Bawaslu Provinsi Kepulauan Riau, 2023)
Democracy in Indonesia continues to develop by strengthening the electoral system as well as strengthening the monitoring and participation system in the implementation of elections. One important step in strengthening democracy is the presence of women present to ensure the quality of democracy. This strengthening of democracy has been accompanied by the increasing involvement of women in various aspects, starting with the increasing number of them becoming members of the legislature, executive, or being involved as part of election management institutions. This development is certainly a positive development, however, if we look at the proportions, the number of women involved in the legislative body is still small. This article argues that there are still socio-cultural barriers for women to be involved in the electoral field. This article uses qualitative analysis and relies on secondary data such as journals, research reports and online articles as a basis for constructing arguments. Political education is provided so that it can be used to hone a person's political abilities and skills, so that they can then participate in party activities and in legislative institutions. This is a manifestation of responsibility to society, constituents and political parties. Women's participation is a form of active action by women cadres in party and government activities which is driven by awareness of political knowledge, so that it results in successful women's political participation. The low participation of women in the Kerinci DPRD legislative body is the basis for this research. The representation of women in the legislative body in Kerinci district is very low, of the 30 legislative members there was only 1 woman in the legislative election results for the 2019-2024 period. Of course the 30% quota is far from being met. The author conducted research using interviews with active female legislative members who are currently serving as members of the DPRD. Using this method, some of the information the author obtained from this research is that society's political culture still tends towards patriarchy, and then women's political will and knowledge still tends to be low.